1998
DOI: 10.1677/joe.0.1560205
|View full text |Cite
|
Sign up to set email alerts
|

Increased corticosteroid binding capacity of plasma albumin but not of corticosteroid-binding globulin caused by ACTH-induced changes in free fatty acid concentrations in snowshoe hares and rabbits

Abstract: Free fatty acids (FFAs) are rapidly mobilized by ACTH and have been shown to be potent endogenous modulators of steroid-protein interactions. We increased FFA in lagomorphs by ACTH and then separated the transient increase in glucocorticoid binding capacity of plasma into that accounted for by changes in binding to albumin and to corticosteroid-binding globulin (CBG). Sequential injections of dexamethasone and ACTH into both snowshoe hares and laboratory rabbits resulted in the rapid mobilization of FFA only a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 30 publications
3
12
0
Order By: Relevance
“…() found a major temporary increase in the maximum corticosteroid‐binding capacity of blood within 30 min following an ACTH injection in wild snowshoe hares. A similar increase was shown in laboratory rabbits (Boonstra & Tinnikov ). By selective degradation of CBG, Boonstra & Tinnikov () showed that the increased CORT binding was entirely owing to changes in the binding properties of albumin, not to changes in CBG binding.…”
Section: Corticosteroid‐binding Globulinsupporting
confidence: 85%
See 3 more Smart Citations
“…() found a major temporary increase in the maximum corticosteroid‐binding capacity of blood within 30 min following an ACTH injection in wild snowshoe hares. A similar increase was shown in laboratory rabbits (Boonstra & Tinnikov ). By selective degradation of CBG, Boonstra & Tinnikov () showed that the increased CORT binding was entirely owing to changes in the binding properties of albumin, not to changes in CBG binding.…”
Section: Corticosteroid‐binding Globulinsupporting
confidence: 85%
“…A similar increase was shown in laboratory rabbits (Boonstra & Tinnikov ). By selective degradation of CBG, Boonstra & Tinnikov () showed that the increased CORT binding was entirely owing to changes in the binding properties of albumin, not to changes in CBG binding.…”
Section: Corticosteroid‐binding Globulinsupporting
confidence: 85%
See 2 more Smart Citations
“…(7), while the other did not (18). Because hypoxia induces hyperlipidemia in suckling rats (26) and hyperlipidemia alters the serum binding of corticosterone (4,13), we repeated these measurements after delipidation of serum using Lipoclear (Statspin, Norwood, MA).…”
Section: Acth Injection and Blood And Tissue Samplingmentioning
confidence: 99%